2012
DOI: 10.1124/jpet.112.193813
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Early Acetaminophen Hepatotoxicity between Obeseob/obanddb/dbMice

Abstract: Clinical investigations suggest that hepatotoxicity after acetaminophen (APAP) overdose could be more severe in the context of obesity and nonalcoholic fatty liver disease. The preexistence of fat accumulation and CYP2E1 induction could be major mechanisms accounting for such hepatic susceptibility. To explore this issue, experiments were performed in obese diabetic ob/ob and db/db mice. Preliminary investigations performed in male and female wild-type, ob/ob, and db/db mice showed a selective increase in hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 60 publications
4
89
2
Order By: Relevance
“…Oxidative stress, including induced by APAP, can secondarily increase the expression of different genes such as heme oxygenase 1, γ-glutamylcysteine synthase, different glutathione S-transferases, heat shock protein 70 and tribbles pseudokinase 3 (Aubert et al, 2012; Chan et al, 2001). Importantly, nuclear factor, erythroid 2-like 2 (NRF2, or NFE2L2) is a transcription factor playing a major role in the regulation of most of these genes (Chan et al, 2001; Ma and He, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress, including induced by APAP, can secondarily increase the expression of different genes such as heme oxygenase 1, γ-glutamylcysteine synthase, different glutathione S-transferases, heat shock protein 70 and tribbles pseudokinase 3 (Aubert et al, 2012; Chan et al, 2001). Importantly, nuclear factor, erythroid 2-like 2 (NRF2, or NFE2L2) is a transcription factor playing a major role in the regulation of most of these genes (Chan et al, 2001; Ma and He, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several investigations in rodents and humans reported that NALFD is associated with more severe APAP-induced hepatotoxicity, especially after an overdose (Aubert et al, 2012; Kon et al, 2010; Michaut et al, 2014; Myers and Shaheen, 2008; NGuyen et al, 2008). Moreover, in vitro investigations showed that steatotic rat hepatocytes in primary culture were more susceptible to APAP-induced acute cytotoxicity (Kucera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that concurrent mutations in other UGTs associated with 1A1 through linkage disequilibrium in some Gilbert’s syndrome patients could account for the differences (54). Interestingly, it was recently shown that obese mice with steatosis have higher expression of UGTs than wildtype controls, and samples from these animals had higher concentrations of APAP-glucuronide (5556). The mechanism by which obesity leads to increased glucuronidation in mice is not yet known.…”
Section: Acetaminophen Metabolismmentioning
confidence: 99%
“…This susceptibility, also found in trib1 morphants, might be APAP specific, but might also be correlated to plasma liver enzyme elevation. For example, liver enzymes increase not only during APAP-induced liver toxicity but also in other types of metabolic or toxic liver injury, and enzyme levels can be further increased by APAP exposure (Aubert et al, 2012; Kučera et al, 2012; Majhi et al, 2011). These functional data might inform further genomic studies to identify differentiating SNPs between pnpla3 and samm50 that could correlate with gene function.…”
Section: Discussionmentioning
confidence: 99%